2011
DOI: 10.5713/ajas.2011.10112
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in the Percentage Content of Edible and Non-edible Components in Broiler Chickens

Abstract: The objective of this study was to determine age-related changes in the percentage content of edible and non-edible components in broiler chickens. The experimental materials comprised 240 Ross 308 chicks (sex ratio 1:1) raised to 10 weeks of age and fed standard diets ad libitum. Starting from the first week of rearing, every 7 days 10 males and 10 females were selected randomly for slaughter and post-slaughter analysis. The data obtained were verified statistically. The percentage content of edible component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 19 publications
6
23
0
5
Order By: Relevance
“…days of age in our study were considerably lighter than Ross 308 chickens of the same age investigated by Murawska et al (2011).…”
Section: Body Conformation and Internal Organs Characteristics Of Difmentioning
confidence: 64%
“…days of age in our study were considerably lighter than Ross 308 chickens of the same age investigated by Murawska et al (2011).…”
Section: Body Conformation and Internal Organs Characteristics Of Difmentioning
confidence: 64%
“…In an earlier study (Abdel-Azeem, 2010) with 35-day-old Japanese quail, both males and females had greater liver weight (4.94 and 5.88 g, respectively) compared to our study. Murawska et al (2011), who analysed age-related changes in percentage of edible and non-edible carcass components of broiler chickens, found that the liver grew rapidly to 8 weeks of age. The weight of gizzard (Table 6) in the analysed birds was similar on both evaluation dates (2.9 g in younger birds and 3.0 g in older birds).…”
Section: Resultsmentioning
confidence: 99%
“…Murawska et al (2011) observed the influence of chicken age and the percentage content of giblets. They found a relationship between increased muscle tissue weights and decreased giblet contents.…”
Section: Discussionmentioning
confidence: 99%